2005
DOI: 10.1007/s00125-004-1630-1
|View full text |Cite
|
Sign up to set email alerts
|

Orosomucoid in urine is a powerful predictor of cardiovascular mortality in normoalbuminuric patients with type 2 diabetes at five years of follow-up

Abstract: Aims/hypothesis: To study whether urinary orosomucoid excretion rate (UOER) predicts mortality in normoalbuminuric patients with diabetes at 5 years of follow-up, and to investigate the relationship between orosomucoid in serum and urine. Methods: A cohort of 578 patients with diabetes (430 type 2, 148 type 1) was followed prospectively for an average of 5 years. UOER was measured in timed overnight urine samples. Results: Eightytwo patients with type 2 diabetes and 17 patients with type 1 diabetes died. Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…An important reason to use suction blister fluid as body fluid in some of these cases, would be that it is much less invasive than biopsies. In these cases, the blisters probably have to be applied near the localized effect [55][56][57]. From Table 1 it becomes clear that various proteins are used to diagnose different diseases and that some proteins can be used to diagnose or monitor multiple diseases.…”
Section: Protein Markers In Suction Blister Fluid Without Additional mentioning
confidence: 99%
“…An important reason to use suction blister fluid as body fluid in some of these cases, would be that it is much less invasive than biopsies. In these cases, the blisters probably have to be applied near the localized effect [55][56][57]. From Table 1 it becomes clear that various proteins are used to diagnose different diseases and that some proteins can be used to diagnose or monitor multiple diseases.…”
Section: Protein Markers In Suction Blister Fluid Without Additional mentioning
confidence: 99%
“…Previously we showed that u-ORM could be a more sensitive marker of inflammation than serum ORM which rises only 2-fold in contrast to even 200-fold increase of u-ORM in sepsis ( 21 ). Others also showed that the elevation of u-ORM is much more considerable than that of serum ORM in relation to inflammatory diseases ( 10 , 11 , 17 ). These results indicate that u-ORM is a reliable marker of chronic and acute inflammatory disorders and provides valuable supplementary information for daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Our subsequent studies showed that orosomucoid is a prominent component of proteinuria in acute heart disease (16 ). Our interest in studying the excretion of urinary orosomucoid in states of acute inflammation was further strengthened by our recent finding that the urinary orosomucoid excretion rate is a strong risk marker for cardiovascular mortality in patients with type 2 diabetes and appears to be a marker of low-grade inflammation in this chronic condition (17,18 ).…”
mentioning
confidence: 98%